Uji Efektivitas Antihiperglikemia Kombinasi Jus Pare (Momordica charantia L) dan Jus Tomat (Solanum lycopersicum L) pada Tikus Wistar Jantan dengan Metode Toleransi Glukosa - Wulandari, Wulandari (Pharmaceutical Sciences and Research, 2016)
Diabetes melitus (DM) is a metabolic disorder condition characterized by hyperglycemia. Bitter melon (Momordica charantia L) and tomato (Solanum lycopersicum L) is a plant that have actvity antihiperglicemic compounds that contain triterpenoid, flavonoid, alkaloid, and saponin. This study was aimed to determine the effect of the combination antihiperglicemic bitter melon juice and tomato juice on male Wistar rats induced sucrose. Animals used are male Wistar Rattus norvegicus healthy in divided into 6 groups . Blood glucose levels were measured at 30th, 60th, 90th and 120th minutes with enzymatic method using a glucometer. Data were analyzed statistically by KruskalWallis and Mann-Whitney compared to the other with a 95% confidence level. Results the MannWhitney test showed a blood glucose level of group negative differ significantly from the other group (P > 0.05 ) and did not differ significantly with group 6 (P > 0.05). Group 5 has a significant difference (P < 0.05) with other groups and more effectively lower blood glucose levels from minute 90th to minute 120th. Group 5 (bitter melon juice 17.4 g/KgBW and tomato juice 16.8 g/KgBW) has the effect of decreasing blood glucose levels better than single juice.